Client satisfaction and associated factors towards the health service provided to members of a community-based health insurance scheme in Southern Ethiopia - Babore, Getachew Ossabo; Ashine, Taye Mezigebu; Heliso, Asnakech Zekiwos; Habebo, Teshome Tesfaye (Frontiers in Health Services, 2023)
Globally, 1.3 billion poor people have no access to health services due to being unable to afford payment when they need services. According to the WHO 2014 report, globally 150 million people are pushed into poverty as a result of direct payment for health services. Objective: to assess clients’ satisfaction level and associated factors towards health service provision among community-based health insurance scheme members. Method: An institutional-based cross-sectional study design was employed. A total of 399 sample size was estimated using a single population formula and three health facilities were selected using a simple random sampling method whereas study participants were selected by applying a systematic sampling method. All patients who visited health facilities were included whereas women who visited health facilities for maternity service were excluded from the study. A Reliability test (Cronbach alpha) was carried out to determine internal consistency for those items to measure clients’ satisfaction was performed. Epi-info software version 7 was used for sample size calculation and data entry whereas further data cleaning and analysis was performed using SPSS software version 20. Result: a total of 367 clients enrolled in community-based health insurance were interviewed which gave a response rate of 93%. The reliability test for the items measured clients’ satisfaction (Cronbach’s alpha) was 0.817. The overall level of clients' mean satisfaction towards health service provision was 63.1% (3.95 + 0.47 SD). This study found age AOR=0.11[95% CI (0.01, 0.79)], residence AOR=1.80 [95% CI (1.79, 3.66)], number of family AOR=2.27 [95% CI (1. 46, 11.22)], frequency of visits to health facilities AOR=13.62 [95% CI (2.09, 88.58)] and clients’ level of knowledge AOR=3.33 [95% CI (1.06, 10, 42) had statistical significant association with client satisfaction towards health service provision. Conclusion: our study found that the perceived level of client satisfaction is higher than previous studies. Leaving address, frequency of visits, level of knowledge, payment during referral time, number of family, and frequency of visits were identified as predictors of clients’ satisfaction on the health service provision.